Impact of COVID-19 lockdowns and aidpackages: Evidence from Viet Nam - Cuong Viet Nguyen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In view of the detrimental effect of COVID-19 lockdowns on household welfare, most countries implemented economic stimulus aid packages to support households. The extent to which these packages mitigated the pandemic's adverse effects on households is not just an intriguing question for researchers but is also important for policy makers. Using individual fixedeffect regressions, I find that an additional month of lockdown reduced per capita income by 8.3 per cent in Viet Nam. Experience of longer lockdowns reduced individuals' satisfaction with provincial government's response to the pandemic. On the other hand, receipt of aid packages enabled households to increase their per capita income by 8.5 per cent. Importantly, receipt of an aid package increased the probability of satisfaction with provincial and commune governments' response to the pandemic by 3.6 and 10.3 percentage points respectively.
Keywords: J21; H84; H53; O38; 330; COVID-19; aid package; lockdowns; household welfare Viet Nam